Motivational factors among undergraduates learning mandarin: a qualitative perspective - Cheong, Kar Mee; Salam, Sazilah; Ithnin, Fazidah; Abdul Bareed, Nurhidayah; Jano, Zanariah; Suraidi, N. (Human Resource Management Academic Research Society, 2019)
Mandarin is an important international language beside English. The purpose of this study was to investigate the motivation of undergraduate students learning Mandarin. A qualitative analysis through interview sessions was used in this study. Four undergraduate students participated in the interview and their transcripts were analyzed to ascertain common themes or categories. The findings showed that “to be ready for future career” and “to be able to communicate with Chinese friend” were two motivational factors for students learning Mandarin. This study is beneficial for Mandarin tutors and instructors in order to determine the content of Mandarin learning materials. In future, a similar study using a triangulation method should be conducted